Evaluasi Kritis Penggunaan Data Hujan Satelit: Pengaruh Kondisi Wilayah Terhadap Akurasi Dan Kelayakan - Maria Kalista Hadia Sabu (Jurnal Teknologi Terpadu, 2026)
Limited rainfall data in eastern Indonesia encourage the use of satellite data as an alternative to support water resource management. This study evaluates the accuracy of nine satellite rainfall products in two regions with contrasting topography: Manggarai Regency (±1,188 m above sea level) and Sikka Regency (±100 m above sea level). Analysis was performed at daily and monthly scales using Pearson correlation, RMSE, NSE, and bias. The results indicate that in Manggarai, none of the products are adequate, either daily or monthly, due to the complexity of the mountainous topography. In contrast, in Sikka, most products perform reasonably well on a monthly scale, although accuracy decreases significantly daily. Based on the comparison matrix, CHIRPS was identified as the best product for monthly rainfall in Sikka. These findings emphasize that the use of satellite data cannot be generalized across regions, so local validation, taking into account topography and temporal resolution, remains necessary.